Costs versus earnings in colon surgery and coronary artery bypass grafting under a prospective payment system: Sufficient financial incentives to reduce surgical site infections?. (22nd August 2018) - Juchler, Fabrice; Roth, Jan A.; Schweiger, Alexander; Dangel, Marc; Gugliotta, Massimo; Battegay, Manuel; Eckstein, Friedrich S.; Kettelhack, Christoph; Abshagen, Christian; Hug, Balthasar L.; Boyce, John M.; Widmer, Andreas F.
Abstract: Based on a surgical site infection (SSI) cohort at an academic center, we showed a median potentially preventable loss per non-SSI case of $17, 916 in colon surgery and of $34, 741 in coronary artery bypass grafting.